2003
DOI: 10.1002/jso.10236
|View full text |Cite
|
Sign up to set email alerts
|

Myocutaneous versus thoraco‐abdominal flap cover for soft tissue defects following surgery for locally advanced and recurrent breast cancer

Abstract: The results of the current study show a significant difference in the blood loss, operating time, and hospital stay between patients requiring TA and MC flap for soft tissue cover following mastectomy. In view of its simplicity and better results, we recommend that the TA flap should be used as a first option flap in advanced breast cancer patients requiring skin cover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 18 publications
(19 reference statements)
0
45
0
Order By: Relevance
“…In a recent review, thoracoepigastric skin flaps used for chest wall coverage of soft tissue defects following surgery for locally advanced and recurrent breast cancer compared favorably to myocutaneous flaps in terms of intraoperative blood loss, operating time, and duration of hospital stay [43].…”
Section: Thoracoepigastric Skin Flapsmentioning
confidence: 99%
“…In a recent review, thoracoepigastric skin flaps used for chest wall coverage of soft tissue defects following surgery for locally advanced and recurrent breast cancer compared favorably to myocutaneous flaps in terms of intraoperative blood loss, operating time, and duration of hospital stay [43].…”
Section: Thoracoepigastric Skin Flapsmentioning
confidence: 99%
“…Deo et al (19) reported that fasciocutaneous flaps are more successful compared with myocutaneous flap due to decreased blood loss during the surgery, a shorter length of the surgery and a shorter hospital stay. Conversely, Martella et al (20) suggested that there is no difference between myocutaneous and fasciocutaneous flaps in regards to local complications and the length of hospital stay required.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, myocutaneous flaps provide enough tissue volume to cover the skin defect and have a good blood supply (2,21). Cutaneous and fasciocutaneous flaps do not require the loss of major muscles and can be completed in a shorter length of time (19). The flap method should be considered and chosen on a case-by-cases basis according to the size of the skin defect and the condition of the recipient/donor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last four decades a variety of surgical techniques have been implemented which include skin grafts, local skin or fasciocutaneous flaps and myocutaneous flaps (such as pectoralis major, rectus abdominis, lattissmus dorsi and external oblique flaps). 1,2 Generally, flaps are advantageous over the skin grafts in terms of aesthetics and durability especially when adjuvant radiotherapy is indicated. [2][3][4][5] The technique of using Latissmus Dorsi myocutaneous flap (LDMF) for closure of defects in oncologic breast surgery was first described by Tansini.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Generally, flaps are advantageous over the skin grafts in terms of aesthetics and durability especially when adjuvant radiotherapy is indicated. [2][3][4][5] The technique of using Latissmus Dorsi myocutaneous flap (LDMF) for closure of defects in oncologic breast surgery was first described by Tansini. 6 In the present study LDMF was used for covering chest wall defects in fifteen patients over a period of two years.…”
Section: Introductionmentioning
confidence: 99%